Outcome of neonatal hypoxemic respiratory failure: a livebirth population-based retrospective survey - Sufang Ding; Yaling Xu; Hui Wang; Hongni Yue; Zhaojun Pan; Bo Sun; on behalf of the Huai'an Perinatal-Neonatal Study Group (BMC, 2022)
Abstract Background To explore the prevalence, outcome and perinatal risks of neonatal hypoxemic respiratory failure (NRF) in a survey of all livebirths from a regional network of perinatal-neonatal care during the transition period after 5-year universal health insurance implemented in China. Methods Clinical data of all neonatal respiratory morbidities in Huai'an were retrospectively collected in the regional perinatal network database of all livebirths as vital statistics in 2015. NRF was defined as hypoxemia requiring continuous positive airway pressure (CPAP) and/or mechanical ventilation (MV) for at least 24 h. Mortality risks of antenatal and perinatal morbidities, major respiratory therapies and complications were analyzed by multivariable logistic regression model. Results There were 788 NRF cases identified in 9.9% (7960) hospitalized, or 13.3‰ (59056) livebirths, in which 6.7% received intensive care and 93.0% critical care. The major underlying morbidities were respiratory distress syndrome (RDS, 36.4%) and pneumonia/sepsis (35.3%), treated mainly by CPAP, MV and surfactant. Significantly improved outcomes by surfactant in RDS were in patients with birthweight (BW) < 1500 g or gestational age (GA) < 32 weeks. The overall mortality rate in NRF was 18.4% whereas for those of BW < 1000 g and GA < 28 weeks, 70% and 54%, respectively. The multivariable regression analysis showed the highest odds for NRF death among meconium aspiration syndrome, congenital anomalies, BW < 1500 g and necrotizing enterocolitis, whereas born in level III hospitals, cesarean delivery, CPAP and MV were associated with markedly reduced death odds. Conclusions The salient findings with associated risk estimates reflected efficiency of respiratory support as critical care in a prefectural regional network infrastructure for annual livebirths in 5.6 million inhabitants. It implicated the representativeness of contemporaneous perinatal-neonatal care standard at medium to medium-high level, in one/fourth of the population of China, aiming at saving more life of very critical and preterm infants for better survival.